Die voorkoms en profiel van pasiënte wat by 'n plattelandse praktyk presenteer met psigosomatiese klagtes - A.D.B. Bruwer; G. Joubert; J.P. Pretorius; M.V.J. van Vuuren (South African Family Practice)
Introduction: The general practitioner is often consulted by patients with complaints in which psychological factors have a significant influence on the origin, continuation or course of a disease. It is important to identify the condition as a psychosomatic disorder, since the patient can be treated more effectively if he or she gains insight into the underlying problem and the causal factor can be addressed. The aim of this study was to determine the prevalence of psychosomatic complaints in patients visiting a general practice. It was also investigated whether variables such as gender, age and population group play a role with regard to the prevalence of the complaints. In addition, it was determined which types of complaints and stressors occur.